2010
DOI: 10.1016/j.jaut.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Mer receptor tyrosine kinase expression leads to enhanced MZ B-cell responses

Abstract: Control of lymphocyte homeostasis is essential to ensure efficient immune responses and to prevent autoimmunity. Splenic marginal zone B-cells are important producers of autoantibodies, and are subject to stringent tolerance mechanisms to prevent autoimmunity. In this paper, we explore the role of the Mer tyrosine kinase (Mertk) in regulating autoreactive B cells. This receptor tyrosine kinase serves to bind apoptotic cells, to mediate their phagocytosis, and to regulate subsequent cytokine production. Mice la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
(41 reference statements)
4
22
0
Order By: Relevance
“…This is consistent with previous data suggesting that MerTK is required in the innate immune system to induce IL-10 following efferocytosis and TLR activation (3, 4, 21, 50, 51). We also showed that MerTK-deficient cells in the tumor microenvironment express increased IL-12 and IL-6, proinflammatory cytokines known to be repressed by MerTK signaling in response to efferocytosis or TLR activation (4,32).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This is consistent with previous data suggesting that MerTK is required in the innate immune system to induce IL-10 following efferocytosis and TLR activation (3, 4, 21, 50, 51). We also showed that MerTK-deficient cells in the tumor microenvironment express increased IL-12 and IL-6, proinflammatory cytokines known to be repressed by MerTK signaling in response to efferocytosis or TLR activation (4,32).…”
Section: Discussionmentioning
confidence: 64%
“…For example, low doses of lipopolysaccharide in MerTK -/-mice resulted in death from endotoxic shock associated with high levels of TNF-α (30). Failure to dampen acute innate immunity leads to secondary pathological activation of T and B lymphocytes directed at self-antigens (4,26,29,31,32). This is especially important given that apoptotic cells accumulate in the absence of MerTK (23,28), providing an enriched source for intracellular "self" antigens in the context of heightened acute inflammatory signals and enhanced B and T lymphocyte activity.…”
Section: Introductionmentioning
confidence: 99%
“…Aged Mer-deficient (Mer -/-) mice that expressed a nonfunctional Mer receptor tyrosine kinase and Mer-deficient DNA-specific immunoglobulin heavy-chain transgenic (3H9.Mer -/-) mice also spontaneously produced DNAspecific Abs of the IgG2a isotype [66]. These data together suggested a possible role for T H 1 lineage differentiation (associated with IFN-c production) in enhancing plasma cell, GC, and IgG2a Ab responses in these mice.…”
Section: Impaired Clearance Of Acs In Gcs Altered B Cell Tolerance mentioning
confidence: 92%
“…It is therefore not surprising that mouse mutants in TAM receptor genes eventually develop broad-spectrum autoimmune disease (Lu and Lemke 2001;Scott et al 2001;Radic et al 2006;Wallet et al 2008;Rothlin and Lemke 2010;Shao et al 2010). This disease, which is particularly severe in Axl 2/2 Mer 2/2 double mutants and in TAM TKOs (Lu and Lemke 2001), has clinical features of both systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA), and is characterized by swollen joints, IgG deposits in the kidneys and other tissues, and pro-…”
Section: Tam Signaling and Autoimmune Diseasementioning
confidence: 99%
“…However, mutational analyses also indicate that tyrosine kinase activity is required for Axl potentiation of infection by Ebola (Shimojima et al 2007) and DENV (Meertens et al 2012), and thus active TAM signaling appears to be required for the potentiation of virus infection just as it is required for the phagocytosis of ACs. Given that (1) Axl activation potently suppresses type I IFN signaling in DCs and macrophages (Sharif et al 2006;Rothlin et al 2007;Shao et al 2010), (2) type I IFNs are strong antiviral agents (Diamond 2003), and (3) suppression of type I IFN signaling is a mechanism that viruses exploit repeatedly as a means of immune evasion (Diamond 2003;Bonjardim et al 2009;Versteeg and Garcia-Sastre 2010), the activation of TAM receptor signaling by viruses may prove to be an exceptionally effective mechanism of viral infection.…”
Section: Tam Receptors As Targets For Viral Infectionmentioning
confidence: 99%